A Century Of Migrant Labour In The Gold Mines Of South Africa - J. S. Harington (The Southern African Institute of Mining and Metallurgy, 2004)
Our purpose is to record and to explain the widely changing numbers of the huge total of black workers on the gold mines of South Africa over the century from 1896 to 1996. These men were recruited from up to twenty territories, and their contributions are examined. The major areas providing labour over this long period have been Lesotho, the former Transkei within South Africa and Mozambique. From 1989 to 1996, for instance, these three areas accounted for over sixty per cent of the total labour force (tlf). Our principal Figure 1 shows the tlf fluctuating through time to reach a peak of 480 000 in 1988. Irregular falls are also documented with the most serious in 1995 to 180 000. Based on this graph we consider the political, economic, sociological and historical reasons behind these changing employment opportunities. These have included external world-scale events such as war or depression, as well as internal changes of national economy and policy. We show the importance for numbers employed of the discovery of gold in the Orange Free State in 1946, the influence generally of the ?Winds of Change? and the firm maintenance by the State of law and order. Varying gold production costs and profitability against high tax rates, allied with increasing wages and a lack of development capital, have led in the last decade to employment falling by fifty per cent, despite an actually higher value of gold output. Finally, this analysis considers the role of the migrant labour system as it affects, and is affected by, conditions in the gold mining industry, with special reference to its less than humane consequences in the numerically dominant territories of Lesotho and Transkei.